2012
DOI: 10.1111/j.1475-2743.2012.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Does returning sites of historic peri‐urban waste disposal to vegetable production pose a risk to human health? – A case study near Manchester, UK

Abstract: Urban waste disposal occurred on fenland to the west of Manchester, England, between 1900 and 1964. The reclaimed fenland, Chat Moss, is now used for mixed arable farming. A total of 1.92 Mt of waste including privy midden, street sweepings, clinkers and slaughterhouse refuse was incorporated into the moss resulting in a modified topsoil with raised pH and reduced organic matter content compared with the subsoil. Elevated levels of potentially toxic elements (PTEs) are observed in the topsoil beyond the typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Normal Ni values in plants are reported to be around 1 mg kg −1 DW [5,54], although Marschner and Marschner [55] refer the critical toxicity levels of Ni as between 10 and 50 mg kg −1 DW, depending on crop species. The values detected in the present work (a maximum of 81.74 mg kg −1 DW) are higher compared to the reported values in lettuce in uncontaminated soils [56,57], although the plants showed no signs of toxicity. In a study of the growth of lettuce in Ni-contaminated soils, Zhao, et al [58] reported Ni levels in leaves similar to the ones obtained in the present study and only detected a reduced growth for Ni mass fractions of 400 mg kg −1 and higher, thus confirming the high tolerance of lettuce plants to Ni.…”
Section: Evaluation Of Vegetable Contaminationcontrasting
confidence: 87%
“…Normal Ni values in plants are reported to be around 1 mg kg −1 DW [5,54], although Marschner and Marschner [55] refer the critical toxicity levels of Ni as between 10 and 50 mg kg −1 DW, depending on crop species. The values detected in the present work (a maximum of 81.74 mg kg −1 DW) are higher compared to the reported values in lettuce in uncontaminated soils [56,57], although the plants showed no signs of toxicity. In a study of the growth of lettuce in Ni-contaminated soils, Zhao, et al [58] reported Ni levels in leaves similar to the ones obtained in the present study and only detected a reduced growth for Ni mass fractions of 400 mg kg −1 and higher, thus confirming the high tolerance of lettuce plants to Ni.…”
Section: Evaluation Of Vegetable Contaminationcontrasting
confidence: 87%
“…Changes in soil chemical properties, chiefly pH arising from agricultural inputs or contaminants, affect many functions. Metals and metalloids can accumulate in topsoil from either the atmosphere or the use of fertilizers, agrochemicals, manures or waste materials on land which, if released in toxic concentrations, particularly under acidifying conditions, can severely impair plant growth and food quality (Pearson & Stewart, ; Blake et al ., ; Blake & Goulding, ; Millennium Ecosystem Assessment, ; Degryse et al ., ; Atkinson et al ., ). Some metals and metalloids are phytotoxic and decrease yields at high concentrations (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Spinach is especially sensitive to metal contamination as is known to be able to grow healthily and at the same time accumulating high amounts of different metals (Pinto et al 2017). In a study comparing the growth of nine different vegetables in waste-amended soils, 4 Atkinson et al (2012) reported that spinach accumulated more heavy metals than other vegetables (except lettuce that accumulated more Cd than spinach). Sinha et al (2007) also found that spinach plants had good yields in contaminated soils with high accumulation of metals in the edible parts .…”
Section: Introductionmentioning
confidence: 99%